Overseeding Florida Lawns for Winter Color - Laurie E. Trenholm; J. Bryan Unruh (EDIS)
Revised! ENH14, a 4-page illustrated fact sheet by L.E. Trenholm and J. Bryan Unruh, describes this practice used to provide green winter turf color for Florida lawns — selecting rye grasses, seedbed preparation, maintenance, and transitioning back to permanent grass. Published by UF Department of Environmental Horticulture, December 2010.